STRATEGI GURU DALAM MENGEMBANGKAN KARAKTER DISIPLIN TERHADAP PESERTA DIDIK - Talia Maulina Dewi (Journal of Education and Learning, 2025)
Education is a fundamental human right that every individual needs to live their life effectively. Education can be formal or non-formal, starting from the family and continuing through school or Islamic boarding schools. This study aims to determine the character of student discipline. In addition, to determine the teacher's strategy in developing a character of discipline through learning activities and identify factors that support and inhibit these strategies. This study uses a descriptive qualitative method with a case study approach, using interviews, observation, and documentation. Data sources include human actions, library materials, and personal data. Based on the results of this study, changes in student attitudes and behavior are reflected in the character of discipline. These changes include punctuality, discipline when entering the classroom, prayer before starting the lesson, greeting, cleanliness, completeness of uniforms, and nail hygiene. Students are also instructed to pick up trash, recite shalawat and Asmaul Khusna before starting the lesson, and perform the sunnah dhuha prayer together.